Português?! Pra que, dona?!: Canções em sala de aula e construção de identidades - Semedo, Larissa Grillo (2019)
Given the objective of investigating the identity construction for both students and teacher in a 6th grade class in Elementary School, observing the meaning given to Portuguese classes, this narrative research proposes a classwork with songs, using the Receptional Method as a theoretical support. A didactic sequence was developed to organize the classwork. Because of the recurrence of students who finish Elementary/Middle School without realizing the importance that the language has in their discourse and social practices; and also because of the wish of making the teaching practice more meaningful for both students and teacher, it was necessary to investigate the construction of identities in Portuguese classes. This research has a proposal of an anthology of songs whose topic is identity as well. These songs are suggestions that aim to contribute to other teachers’ classwork with the mother tongue in Elementary/Middle School. Even though the (re)signification of mother tongue classes have happened, it is not a fully finished process, since it depends on an individual that is constantly changing.